MAKANAN ḤALĀL DAN ṬAYYIB PERSPEKTIF AL-QUR'AN DAN RELEVANSINYA DENGAN MAKAN BERGIZI GRATIS (STUDI TAFSIR TEMATIK) - Hafidz Fadhil Bayhaqi; Eka Prasetiawati; M. Agus Mushodiq (CV. Bimbingan Belajar Assyfa, 2026)
The Qur’an establishes the principles of ḥalāl and ṭayyib as inseparable foundations in regulating food consumption, highlighting that Islamic dietary guidance extends beyond legal permissibility to include nutritional value, hygiene, safety, and overall well-being. This research seeks to explore the Qur’anic understanding of these two concepts through the thematic (mauḍū‘ī) interpretation approach while assessing their significance in relation to Indonesia’s Free Nutritious Meal Program (Makan Bergizi Gratis or MBG) as a strategy for improving public nutritional status. Employing qualitative library research, the study examines selected Qur’anic passages, including Surah Al-Baqarah (2:168), Surah Al-Mā’idah (5:88), and Surah An-Naḥl (16:114), together with authoritative classical and contemporary tafsir references. The analysis reveals that ḥalāl primarily concerns the religious legitimacy of food and its lawful means of acquisition, whereas ṭayyib reflects broader dimensions such as nutritional adequacy, cleanliness, food quality, safety, and their positive influence on physical as well as spiritual health. Consequently, the Qur’an presents an ideal dietary framework in which lawful status and wholesome quality must coexist. Within the context of the MBG initiative, these findings underscore the importance of ensuring that meals satisfy not only nutritional requirements but also the Islamic standards of ḥalāl and ṭayyib. Integrating these Qur’anic principles into food policy is expected to strengthen public health outcomes while reinforcing religious and ethical values. Accordingly, this study argues that collaboration between Islamic teachings and modern nutritional science is indispensable for designing food policies capable of fostering a healthy, resilient, and ethically responsible generation.